THE EFFECTS OF PRENATAL LEAD EXPOSURE ON THE DEVELOPMENT OF BIOMARKERS OF ALZHEIMER’S DISEASE - Wood, Andrew (My University, 2015)
While often well known for its adverse effects on memory, Alzheimer’s disease (AD) is also noteworthy for being the sixth leading cause of death in the United States. An estimated 5.2 million Americans had the disease as of 2013, with the number of cases expected to increase in coming decades. Research into the condition has not revealed its exact cause; however, AD is believed to result from a combination of genetic vulnerabilities and environmental influences. An important aspect of AD and this study is the development of plaques or clumps of amyloid beta (AΒ) protein in the brains of those with AD, with increased concentrations of AΒ indicating a more severe condition. Microglia, resident immune cells of the brain, are thought to influence the level of these proteins in the brain. Prenatal exposure to environmental contaminants may influence the actions of microglia during an organism’s lifetime in a way that encourages the development of AD and its observable plaques. This study explored both the separate and combined effects of environmental agents and genetic predispositions to the disease. This was done by exposing both 3x-Tg-AD mice, that have a genetic predisposition to developing AD, and wild-type mice to lead prenatally. The level of AΒ-42 in brains was measured by ELISA at varying ages, and the differences in AΒ-42 was compared between wild-type and transgenic animals between doses for each age and each sex. The final results showed a significant increase in AB-42 concentration in fully mature 3x-Tg-AD mice that were exposed to lead. This evidence supports our hypothesis that developmental exposure to an exogenous contaminant prenatally would exacerbate the tendency of genetically vulnerable organisms to develop the pathologies of AD.
Keywords: Alzheimer's disease; Amyloid beta; Penatal lead exposure; Amyloid-β